2023
DOI: 10.55729/2000-9666.1155
|View full text |Cite
|
Sign up to set email alerts
|

Case report of Acute Q fever with Hepatitis progressing to Chronic Q fever with Endocarditis

Abstract: A 35-year-old male greenhouse worker presented with myalgia, fatigue, and fever. Initially, he was thought to have an unspecified viral infection and was treated with conservative therapy. However, the patient’s symptoms persisted, and he reported additional symptoms of mild abdominal pain and headaches. Laboratory evaluation was significant for elevated liver enzymes. Due to concern for acute hepatitis and persistent fever the patient was hospitalized. During his hospital course, no infectious etiology was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Doxycycline 0.1g bid is the preferred treatment option for acute Q fever, and fluoroquinolones and sulfamethoxazole are also available for a 14-day course. Doxycycline 0.1g bid coupled with hydroxychloroquine 0.2g tid is recommended for chronic Q fever for at least 18 months, particularly Q fever endocarditis ( Patil and Regunath, 2022 ; Jama et al., 2023 ). A recent case report showed that azithromycin can treat myocarditis in chronic Q fever infection ( Steffen et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline 0.1g bid is the preferred treatment option for acute Q fever, and fluoroquinolones and sulfamethoxazole are also available for a 14-day course. Doxycycline 0.1g bid coupled with hydroxychloroquine 0.2g tid is recommended for chronic Q fever for at least 18 months, particularly Q fever endocarditis ( Patil and Regunath, 2022 ; Jama et al., 2023 ). A recent case report showed that azithromycin can treat myocarditis in chronic Q fever infection ( Steffen et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%